Adaptive reasoning of vocational students in solving mathematical logic problems viewed from work readiness - Ashlahul Ummah; Dewi Hamidah; Muhammad Khoiril Akhyar (Institut Teknologi Dirgantara Adisutjipto, 2026)
Adaptive reasoning is essential in mathematical problem solving, especially mathematical logic, yet research on vocational students from a work-readiness perspective remains limited. This study describes the adaptive reasoning ability of eleventh-grade Visual Communication Design (DKV) students in solving mathematical logic problems based on work readiness levels. A descriptive qualitative approach was used with 13 DKV students at a vocational high school in Gresik, Indonesia. Data were collected through a validated work readiness questionnaire, mathematical logic test, and semi-structured interviews. Six students were selected as subjects: two each with high, moderate, and low work readiness. Data were analyzed through reduction, presentation, conclusion drawing, and triangulation. Results show that high-readiness students generally met five adaptive reasoning indicators, moderate-readiness students met four, and low-readiness students met three. The findings support adaptive reasoning-based mathematics learning to strengthen logical reasoning, argument validation, symbolic representation, and workplace readiness.